Age and gender differences in half-Ironman triathlon performances – the Ironman 70.3 Switzerland from 2007 to 2010 - Knechtle B; Rüst CA; Rosemann T; Lepers R (Dove Medical Press, 2012)
Beat Knechtle,1,2 Christoph Alexander Rüst,2 Thomas Rosemann,2 Romuald Lepers31Gesundheitszentrum St Gallen, St Gallen, Switzerland; 2Institute of General Practice and Health Services Research, University of Zurich, Zurich, Switzerland; 3INSERM U1093, Faculty of Sport Sciences, University of Burgundy, Dijon, FranceBackground: To date, the age-related decline and gender differences in performance have been investigated for both Olympic and Ironman distance triathlons, but not for the intermediate distance (ie, the half-Ironman distance triathlon covering 1.9 km swimming, 90 km cycling and 21.1 km running, Ironman 70.3®). We determined the age-related differences in performance and the gender differences for female and male half-Ironman triathletes of 6303 finishers (1115 women and 5188 men) at the Ironman 70.3 Switzerland in Rapperswil, Switzerland, from 2007 to 2010.Methods: Analyses of variance were used to examine performance trends and differences between the genders.Results: Gender differences in total event time were affected by age (F = 4.2; P < 0.001). Women achieved their best performance between 25 and 39 years whereas men attained their fastest race times between 18 and 39 years. The gender difference for ages 18–24 years was significantly (P < 0.01) greater compared to older age groups (25–29 years and 40–44 years), and the gender difference for age groups 45–49 years and 50–54 years was significantly (P < 0.01) greater than for those between the ages of 35–39 years.Conclusion: The present data suggest that the fastest race time in a half-Ironman triathlon was achieved between the age of 25 and 39 years for women and between 18 and 39 years for men. Further studies considering the influences on endurance performance are required to better understand the age and gender interactions in half-Ironman triathlon performances, and these studies may provide valuable information to delineate the difference in performance between female and male half-Ironman triathletes.Keywords: cycling, endurance, female, male, running, swimming